Pendampingan Edukasi Learning-Independence (Belajar Mandiri) pada Pelajar Bahasa Arab - Fina Aunul Kafi; Zulfa Faridhatul Husna (An-Nuqthah, 2021)
This assistance is provided to students of Madrasah Ibtidaiyah who live in Sarimulyo Village, Jombang Jember. To get rid of dependence in learning Arabic, students need assistance that is directed to train them how to learn Arabic independently through the vocabulary of surrounding objects and pronounce it correctly. This service research aims to educate students of Madrasah Ibtidaiyah in learning Arabic independently and to train them to make Arabic language media to hone their creativity in learning. This service research used the community development method. The results of this mentoring activity showed the potential to overcome problems in learning Arabic in madrasas, trigger motivation to learn Arabic, and foster the creative spirit of the assisted students.